(De-)Activating the growth machine for redevelopment: The case of Liede urban village in Guangzhou. (May 2018) - Guo, Youliang; Zhang, Chengguo; Wang, Ya Ping; Li, Xun
This research investigates the mechanism of urban village redevelopment in south China. Through a revised typology of place entrepreneurs based on the growth machine thesis and a case study of Liede village in central Guangzhou, it illustrates how land-based interests embedded in an imbalanced power relationship can (de-)activate urban village redevelopment. The study reveals that while urban villagers, as represented by the village collective, have entrenched interests in the redevelopment process, the city government – as monopolistic land manager and place entrepreneur – plays the deciding role in forging and halting a growth machine geared towards urban village redevelopment. Although developers are also part of the process, the (de-)activation of redevelopment growth machine/coalition in Guangzhou has largely been dominated by the city government. With a comparative view on the original growth machine model, it is hoped that this study would furnish both theoretical and practical thoughts for future research.